Cultivating Lost Land: Livelihood and Depopulation on São Jorge Island, Azores - Burger, Tim (University of Cambridge, 2023)
This ethnography of rural social life on São Jorge Island, Azores, examines the interconnections between depopulation, people’s practices of material livelihood, and their understandings of their overall historical and social condition. Following decades of transatlantic outmigration and demographic decline, subsistence farmers in my main fieldsite, the village of ‘Fajã’, shared a focus on overall decay. However, they evaluated and lived out what I call ‘depopulated social relations’ in different and conflicting ways. This study explores the heterogeneous range of reflexive, hands-on, and often counterintuitive modes in which island residents organized their historical consciousness around the social reproduction of agrarian livelihoods in unfavourable circumstances. My interlocutors’ central predicament was that their intensely valued agrarian land was being overgrown by brushwood. They often described this land as “already lost” (*já perdido*). Watching the physical change of their gardens and terraces was an unsettling and confusing experience that metonymically condensed broader concerns about the moral imperative of agricultural labour, the lack of desirable conviviality, the gendered dynamics of household subsistence, or sacred spacetime. A collective sense of failure regarding agrarian cultivation was the key category through which island residents made sense of depopulation. While gardening hence became a positively imbued activity in which people acted out their historical consciousness, other economic practices such as renting out houses to tourists or intensive cattle farming were more ambivalent in moral quality. Chapters One and Two approach these conflicting forms of livelihood-making through the lenses of land and households, respectively. I argue that the dominant asset for realizing wealth, public distinction, and moral selfhood has shifted from subsistence gardens to houses, producing novel forms of inequality and social heterogeneity. Chapter Three examines outmigration, which people held to ...